Jeffersonians in Power : The Rhetoric of Opposition Meets the Realities of Governing - Neem, Johann N.; Freeman, Joanne B., 1962- (Book collections on Project MUSE., 2019)
"In the 1790s, the Jeffersonian Republicans were the party of 'no.' They opposed attempts to expand the government's role in society. They criticized the Washington Administration's national bank and railed against a standing army. They bemoaned the spirit of the Federalist regime, which, they claimed, favored the wealthy over ordinary Americans. Thus Thomas Jefferson's conviction that his election as President in 1801 was a 'revolution.' With Jeffersonians in power, the nation could be set right. The government could be stripped down in size and strength. But there was a paradox at the heart of this image. Maintaining the security, stability, and prosperity of the republic required aggressive statecraft--to open trade channels and create freer markets and to expand westward onto land claimed by Native Americans and European empires. Jeffersonians deployed state power to reduce taxes and the debt, enforcing a shipping embargo, going to war, and ultimately supporting a national bank during Madison's administration. This book explores this paradox to understand the logic and logistics of Jeffersonian statecraft. 'Jeffersonians in Power' aims at a middle ground. Focusing on statecraft in action, it explores the meeting place of ideology and policy as Jeffersonians shifted from being an oppositional party to exercising power as the ruling coalition"--